ЕРТЕ ДӘЎИРДЕГИ ШЫҒЫС ӘДЕБИЯТЫНДА ҚУСЛАР ОБРАЗЫНЫҢ ЖАСАЛЫЎЫ - Арзыев, Ш.А. (ILIM hám JÁMIYET, 2022)
In legends and stories found in ancient Turkic and Oriental literature, the image of birds and animals is often given in a figurative sense, but later in classical literature it is depicted more symbolically. This article discusses the formation of the image of birds as an image in fiction in antiquity, its influence on the content of works. The interpretation of the image of birds in works of art, along with many other artistic images, speaks of the unique skill of the creators in creating the image.